Strengthening Adolescent Wellbeing project—Qualitative outcomes from a pilot in a Swedish upper-secondary school. (2nd October 2019) - Kristiansen, Lisbeth; Willmer, Mikaela; Karlström, Annika
Abstract : While a majority of Swedish school children enjoy a good health, mental health problems are increasing among young people in Sweden. According to Swedish law all school staff members (teachers and student health professionals) have mutual responsibility to provide a safe school environment and health. Since 2010, there is an emphasis on health promotion in schools. The aim of this study is to qualitatively describe the feasibility of a health-promoting intervention targeting healthy high school students (the Strengthening Adolescent Wellbeing [SAW] project). A descriptive design was used with an intervention group that was assessed before and after the implementation of the programme using quantitative methods. The study was based on the Medical Research Council Framework. The study and the data collection were performed during the autumn of 2016 and the early spring of 2017. Public high school students' health professionals (school nurses), student counsellors and specialist educators, facilitated a research-based intervention consisting of eight sessions with education and mind-body practices. Pre- and post-testing were carried out. The main findings showed that participating students and staff members were satisfied that the content and the implementation of the intervention were meaningful.